Faktor-Faktor Yang Mempengaruhi Fraudulent Financial Reporting - Wulanda Maya Sari; Anik Irawati (Akuntabilitas, 2021)
This study aims to empirically prove the influence of financial stability, external pressure, and ineffective monitoring on fraudulent financial reporting. Financial stability was measured using a comparison of total assets. External pressure was measured using leverage. Meanwhile, ineffective monitoring was measured using the ratio of independent commissioners’ number. The dependent variable in this study was fraudulent financial reporting. It was measured using the F-Score Model. The sample in this study were 21 State Owned Enterprises (BUMN) listed on Indonesia Stock Exchange in period of 2017-2019. The data analysis method used in this study was Logistic Regression using SPSS software version 20. The results of this study indicate that financial stability has no influence on fraudulent financial reporting. Meanwhile, external pressure and ineffective monitoring influence fraudulent financial reporting.How to cite:Sari, W. M., & Irawati, A. (2021). Faktor-faktor yang Mempengaruhi Fraudulent Financial Reporting. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 139-152.